simplest form

posted by .

6x*2-11x+3
__________
6x-9

thats a fraction and ur trying to simplify it

Is that 6x2 or
6x*2= 12x.

9 over 36

18/21

  • simplest form -

    what is 84/100 in simplest form?

  • simplest form -

    whats 8/9 in simplest form?

  • simplest form -

    10/12

  • math -

    what is the simplest form of 7540/94710

  • math -

    754/9471

  • simplest form -

    it takes 36 nails to weigh a pounds.how many nails would it take to weigh 7 2\3 pounds?

  • simplest form -

    1/8*2/3

  • simplest form -

    how do u put 9 and 36 in simplest form

  • simplest form -

    wat is 0.19 in its simplest form Lol soz im dumb

  • simplest form -

    14

  • simplest form -

    whats the simplest form for 4o.330 >;( mixed number

  • simplest form -

    -15 - 23

  • simplest form -

    (-2)(5)(-6)

  • simplest form -

    94,710 over 7,540

  • simplest form -

    find 3/4 + 1/6 simplest form

  • simplest form -

    its easy just focus. all you have to do is add or subtract or divide or miltiply it. Then, you like example : 4 6/8 - 2 1/8 = 2 5/8. if you need anything just ask me im your friend.

  • simplest form -

    18/21

  • simplest form -

    554498

  • simplest form -

    what is 10/12 in its simpliest form?

  • simplest form -

    8/22

  • simplest form -

    4/6

  • simplest form -

    60/84

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Property of logarithms

    Using property of logarithms, how do I prove derivative of ln(kx) is 1/x First observe that ln(kx) = ln(k) + ln(x) then take derivatives. The ln(k) is simply a constant so it goes away. You could also derive it as d/dx ln(kx) = 1/kx …
  2. calc

    Where do I start to prove this identity: sinx/cosx= 1-cos2x/sin2x please help!! Hint: Fractions are evil. Get rid of them. Well, cos2x = cos 2 x - sin 2 x, so 1-coscx = 1 - cos 2 x - sin 2 x = 1 - cos 2 x + sin 2 x You should be able …
  3. Derivatives

    What is the fourth derivative of f(x)= e^-x^2. I got f''(x)=-2e^-x^2 + 4x^2e^-x^2 i need some help on find f''''(x) You have f(x) = e -x 2 then f'(x) = -2x*e -x 2 = -2x*f(x) f"(x) = (4x 2 - 2))e -x 2 = f(x)*(4x 2 - 2)) f"'(x)= f'(x)*(4x …
  4. Math

    Simplify: 4^(-1/2) 4 -1/2 = 1/4 1/2 = 1/2. check my work. On exponents, negative means reciprocal. 4 (-1/2) means the same as 1/4 (1/2) which is the same as 1/squareroot(4) so the answer is 1^4 no, of course not. The square root of …
  5. Inter. Algebra

    Count Iblis what is the answer to 2 square root sign 18x?
  6. Powers in Math

    (5a^3b^4)^2=? *I don't get this one...PLease Help! (5a 3 b 4 ) 2 = (5) 2 *(a 3 )3 2 *(b 4 ) 2 = 25*a 6 b 8 I hope this turns out right. With all of these exponents it is easy to forget to turn them off and or to put parentheses in
  7. algebra

    How do you factor 4x(squared)+12x+40? Thanks! 4x 2 +12x+40= 4(x 2 +3x+10) Is there any way to get it like ( ) *( )?
  8. math exponents

    x to the - power x to the fraction power x to the -fraction power how are they different?
  9. math-volume

    I'm confused with how to solve this problem, so help would be great! The volume of any spherical balloon can be found by using the formula V= 4/3 pi r^3. Write an equation for r in terms of V and pi 4/3*pi*r 3 = V Multiply by 3 3*(4/3)*pi*r …
  10. help

    Y^3Y/Y^-2 If you post with the correct word in the Subject line, you'll usually get help faster. Y^6 Move the denominator to the top.. y 3 Y 1 y +2 = y 3+1+2

More Similar Questions